Respuesta :

Answer:

its k haha

Step-by-step explanation:

Answer:

x = 20

y = -12

Step-by-step explanation:

2x + 2y = 16 -------eqn 1

2x + y = 28 ----------eqn 2

From eqn 2, let's make y the subject of the formula

2x + y = 28

y = 28 - 2x

Substitute the value of y into eqn 1

2x + 2y = 16

2x + 2(28 - 2x) = 16

2x + 56 - 4x = 16

Collect like terms

2x - 4x = 16 - 56

-2x = -40

- cancels -

2x = 40

Divide both sides by 2 to get the value of x

2x/ 2 = 40/ 2

x = 40/2

x = 20

Substitute the value of x = 20 into eqn 2

2x + y = 28

2 (20) + y = 28

40 + y = 28

y = 28 - 40

y = - 12

Therefore,

x = 20

y = -12

Hint, to prove this values, let's pick eqn 1

2x + 2y = 16

x = 20

y = -12

2 ( 20) + 2(-12)

40 - 24 = 16

So our values are correct

ACCESS MORE